Cross‐resistance patterns to acetyl coenzyme A carboxylase (ACCase) inhibitors associated with different ACCase mutations in Beckmannia syzigachne. (24th June 2015) - Pan, L; Li, J; Zhang, T; Zhang, D; Dong, L Y
Summary: Beckmannia syzigachne (American sloughgrass) is a competitive grass weed found in China. Fenoxaprop‐P‐ethyl is widely used for control of this species in China. Resistance to fenoxaprop‐P‐ethyl in B. syzigachne has been reported to be conferred by an isoleucine(Ile)‐1781‐leucine(Leu) substitution in the gene encoding the herbicide target, acetyl‐CoA carboxylase (ACCase). In this study, three mutations were detected by derived cleaved amplified polymorphic sequence (dCAPS) method in fenoxaprop‐P‐ethyl‐resistant B. syzigachne populations: Ile‐1781‐Leu in population JCWL‐R, Ile‐2041‐Asn in JCJT‐R and Gly‐2096‐Ala in JYJD‐R. The data indicated they were genetically homogeneous (homozygous mutant) at the ACCase locus. The use of cytochrome P450 inhibitors was shown to slightly reduce the GR50 value of fenoxaprop‐P‐ethyl‐resistant populations, from which we inferred a combination of target‐site resistance (TSR) and non‐target‐site resistance (NTSR) was involved in fenoxaprop‐P‐ethyl‐resistance. We characterised the cross‐resistance patterns to ACCase inhibitors in B. syzigachne . The plants in the JCWL‐R population were highly resistant to all tested APPs (aryloxyphen‐oxypropionates), sethoxydim and pinoxaden, and moderately resistant to clethodim. The plants in the JCJT‐R population were highly resistant to fluazifop‐P‐butyl, clodinafop‐propargyl, cyhalofop‐butyl, metamifop and pinoxaden; moderately resistant to haloxyfop‐R‐methyl, quizalofop‐P‐ethyl and sethoxydim; and sensitive to clethodim. The plants in the JYJD‐R population were highly resistant to clodinafop‐propargyl, metamifop and pinoxaden; moderately resistant to haloxyfop‐R‐methyl, cyhalofop‐butyl, quizalofop‐P‐ethyl, fluazifop‐P‐butyl and sethoxydim; and sensitive to clethodim. If resistance to ACCase inhibitors is present in B. syzigachne populations in the field, then our results indicate that clethodim should be used. While we demonstrated the cross‐resistance patterns of TSR resulting from three mutations in B. syzigachne, we also demonstrated that NTSR plays a role in resistance, which will complicate weed management.